2021
DOI: 10.1002/biot.202100400
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin biosynthesis from ferulic acid by engineered Saccharomyces cerevisiae

Abstract: Background and Goal: Curcumin is a polyphenolic compound found in Curcuma longa.This bioactive molecule has several reported health-benefit effects, being the anticarcinogenic activity among the most promising ones. However, curcumin extraction from natural sources is hampered by impure products obtained from harsh chemicals and limited by plant seasonality and high prices. Therefore, curcumin heterologous production emerged as an interesting alternative. Escherichia coli has been explored as chassis but the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Compared to the glycerol route, this route has the advantage of not needing B 12 vitamin as a cofactor. However, it is well known that malonyl-CoA availability is limited in microorganisms due to tight regulation of fatty acid biosynthesis [88][89][90]. This low availability limits 3-HP production, whereby most of the studies focus on increasing malonyl-CoA concentration, for example, by overexpressing the enzyme acetyl-CoA carboxylase (ACC) [41][42][43]86,87].…”
Section: Malonyl-coa Routementioning
confidence: 99%
“…Compared to the glycerol route, this route has the advantage of not needing B 12 vitamin as a cofactor. However, it is well known that malonyl-CoA availability is limited in microorganisms due to tight regulation of fatty acid biosynthesis [88][89][90]. This low availability limits 3-HP production, whereby most of the studies focus on increasing malonyl-CoA concentration, for example, by overexpressing the enzyme acetyl-CoA carboxylase (ACC) [41][42][43]86,87].…”
Section: Malonyl-coa Routementioning
confidence: 99%
“…Recently, Rainha et al (2021a) reported the production of curcumin from ferulic acid in the model yeast Saccharomyces cerevisiae. In this work, two different pathways were tested: the first one composed by 4CL1 from A. thaliana and CUS and the other composed by the same 4CL in combination with DCS and CURS1 from C. longa.…”
Section: Other Organismsmentioning
confidence: 99%
“…[ 3,4 ] In addition to glycoside compounds such as acteoside and catalpol, R. glutinosa also contains a large group of phenolics with strong biological activity, including ferulic acid (4‐hydroxy‐3‐methoxycinnamic acid, FA). [ 2,5 ] Especially, FA is an important precursor of some medicinal ingredients, such as coumarins, curcuminoids, vanillins, and lignans, [ 5–9 ] which can exhibit a wide range of biomedical effects, including antioxidant, free radical scavenging, anti‐inflammatory, and antiviral activities. [ 5–8 ] As the FA production in plants including R. glutinosa occurs at low efficiency, [ 2,9 ] it is very significant to explore the FA biosynthesis pathways for enhancing the production of FA and its derivations.…”
Section: Introductionmentioning
confidence: 99%